2016
DOI: 10.7287/peerj.preprints.1789v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Invasion of the tropical earthworm Pontoscolex corethrurus (Rhinodrilidae, Oligochaeta) in temperate grasslands

Abstract: The tropical earthworm Pontoscolex corethrurus presents a broad distribution (56 countries from four continents) with climates that resemble the one in its native area of distribution. In invasive earthworms, it is generally assumed that temperature appears to limit the success of tropical exotic species in temperate climates. With the global climate change, the edge of the distribution range of this species could advance towards higher elevations (with lower temperatures) where no tropical species currently o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Liu and Zou [45] and Ganihar [46] reported that this species prefer soils rich in terms of organic matter and leaf litter content. The present study also corroborates with finding of Ortiz-Gamino et al [47] and reported 8 to 8.4% range of organic matter. Ayala and Barois [48] observed that P. corethrurus was unable to grow in soil with 75-100% organic matter content.…”
supporting
confidence: 93%
“…Liu and Zou [45] and Ganihar [46] reported that this species prefer soils rich in terms of organic matter and leaf litter content. The present study also corroborates with finding of Ortiz-Gamino et al [47] and reported 8 to 8.4% range of organic matter. Ayala and Barois [48] observed that P. corethrurus was unable to grow in soil with 75-100% organic matter content.…”
supporting
confidence: 93%
“…Studies developed in Argentina (Masin et al, 2011;Maitre et al, 2012;Bedano and Domínguez, 2016;Domínguez et al, 2018) and in other regions of the world (Bartz et al, 2013;Lemtiri et al, 2014;Bertrand et al, 2015;Kanianska et al, 2016;Xie et al, 2018) show that earthworm populations are conditioned not only by the edaphic properties and the type of vegetation but also by the history and intensity of land use. In this sense, the studies by Butt and Lowe (2004), García-Pérez et al (2014), andOrtiz-Gamino et al (2016) report that, while earthworm populations are conditioned by some edaphic properties, they are highly sensitive to the anthropic disturbance generated in their ecosystems, thus providing valuable information as bioindicators of soil quality (or soil health). In particular, Bertrand et al (2015) reported that the composition of earthworm populations (number of individuals, proportion of juveniles or adults) depends on both production system and tillage intensity and frequency, and also that population density is affected by changes in vegetation, crop residues quantity and quality, and grazing activities.…”
Section: Introductionmentioning
confidence: 99%
“…In southern regions, climate change will less likely facilitate the spread of alien earthworms from Asia and Europe. However, warming of temperate areas may open colonization opportunities for tropical alien earthworm species, as already observed in a few temperate grasslands 57 .…”
Section: Discussionmentioning
confidence: 88%